"A COMPARATIVE ANALYSIS OF PREPOSITIONS IN ENGLISH AND UZBEK LANGUAGES" (Ustozlar uchun, 2026)
This article presents a comparative analysis of prepositions in English and Uzbek languages. The study examines their syntactic functions, semantic features, and the ways grammatical relations are expressed in both languages. The findings show that English relies heavily on prepositions to indicate grammatical and semantic relationships, whereas Uzbek mainly uses postpositions and case endings for the same purpose. The results of the study are significant for linguistic typology, translation studies, and foreign language teaching.